2020
DOI: 10.1038/s41598-020-65824-1
|View full text |Cite
|
Sign up to set email alerts
|

Motor axonopathies in a mouse model of Duchenne muscular dystrophy

Abstract: Materials and Methods experimental animals. All mice were approved by the Duke University Institutional Animal Care and Use Committee (IACUC) under protocol A233-171-10. All experiments were performed in accordance with relevant guidelines and regulations. All protocols involving mice were approved by Duke University IACUC. C57Bl6/J, wildtype, and C57Bl/10ScSn-Dmd mdx /J (mdx), mice were obtained from the Jackson Laboratory and housed at the Duke University Division Laboratory Animal Resources.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Dystrophin deficiency also causes motor neuron axonopathy of the respiratory nerves. Motor neuron axonopathy is present in both the phrenic and hypoglossal (XII) nerves, which implies that an underlying neuropathology also contributes to the characteristic respiratory failure of DMD (Dhindsa et al., 2020). Further, there is significant demyelination and loss of large‐calibre axons in these mice.…”
Section: Dystrophin‐deficient MDX Mousementioning
confidence: 99%
See 2 more Smart Citations
“…Dystrophin deficiency also causes motor neuron axonopathy of the respiratory nerves. Motor neuron axonopathy is present in both the phrenic and hypoglossal (XII) nerves, which implies that an underlying neuropathology also contributes to the characteristic respiratory failure of DMD (Dhindsa et al., 2020). Further, there is significant demyelination and loss of large‐calibre axons in these mice.…”
Section: Dystrophin‐deficient MDX Mousementioning
confidence: 99%
“…Further, there is significant demyelination and loss of large‐calibre axons in these mice. Finally, mitochondrial abnormalities were evident in the phrenic and hypoglossal nerves (Dhindsa et al., 2020).…”
Section: Dystrophin‐deficient MDX Mousementioning
confidence: 99%
See 1 more Smart Citation
“…While we measured protein levels in dystrophic nerves that innervate limb skeletal muscles, a recent study using electron microscopy describes striking pathological changes in phrenic and hypoglossal (XII) nerves of mdx mice (n=3) aged 12 months (Dhindsa et al, 2020), with severe axonal demyelination and mitochondrial abnormalities that were pronounced for large calibre axons, and it was concluded that this degeneration was initiated at the NMJ.…”
Section: Comparison With Other Dystrophic Nervesmentioning
confidence: 99%
“…Respiratory failure is the leading cause of premature death in severe muscular dystrophy. Studies in the mdx mouse and related models have revealed that respiratory compromise arises owing to dysfunction at multiple levels of the respiratory control network (Burns et al., 2017; Dhindsa et al., 2020). Sleep‐disordered breathing is common in DMD, and exposure to resultant chronic intermittent hypoxia is likely to exacerbate deficiencies in respiratory system performance.…”
mentioning
confidence: 99%